2011
DOI: 10.2174/156720111793663624
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin Receptor-Mediated Imaging and Cytotoxicity: Review and Current Status

Abstract: The three mammalian bombesin (Bn) receptors (gastrin-releasing peptide [GRP] receptor, neuromedin B [NMB] receptor, BRS-3) are one of the classes of G protein-coupled receptors that are most frequently over-express/ectopically expressed by common, important malignancies. Because of the clinical success of somatostatin receptor-mediated imaging and cytotoxicity with neuroendocrine tumors, there is now increasing interest in pursuing a similar approach with Bn receptors. In the last few years then have been mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
209
0
7

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(222 citation statements)
references
References 126 publications
1
209
0
7
Order By: Relevance
“…A variety of radiolabeled BBN analogs have been developed for targeting GRPR-positive tumors and were evaluated in preclinical and clinical studies (5). Several recent reports have shown that GRPR antagonists show properties superior to GRPR agonists, affording higher tumor uptake and lower accumulation in physiologic GRPR-positive nontarget tissues (11,12).…”
mentioning
confidence: 99%
“…A variety of radiolabeled BBN analogs have been developed for targeting GRPR-positive tumors and were evaluated in preclinical and clinical studies (5). Several recent reports have shown that GRPR antagonists show properties superior to GRPR agonists, affording higher tumor uptake and lower accumulation in physiologic GRPR-positive nontarget tissues (11,12).…”
mentioning
confidence: 99%
“…In vitro usage to identify prostate cancer indicates positive identification in 60-100 % [35][36][37][38][39]. Similarly, GRP and BB 3 receptors have been identified in 7/10 and 2/10 gastrinomas, respectively, NMB receptors have been found in 11/27 ileal, while BB3 receptors were the predominant receptors described in 10/29 bronchial NETs [36].…”
mentioning
confidence: 96%
“…More than 40 different bombesin analogs, agonists and antagonists labeled with 99m Tc or with 68 Ga have been evaluated in vitro. They comprise an additional potential class of radiopharmaceuticals for NET imaging [37].…”
mentioning
confidence: 99%
“…Anal ogs of the frog tetradecapeptide bombesin (BBN) have been exploited as molecular vehicles to direct diagnostic and therapeutic radionuclides to human primary and metastatic cancer (1)(2)(3). This approach relies on the high-density expression of gastrin-releasing peptide receptors (GRPRs) in many frequently occurring human cancers, such as prostate cancer, mammary carcinoma, or small cell lung cancer, as opposed to their lower abundance or lack of expression in surrounding healthy tissue (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…These analogs indeed showed high affinity for the human GRPR, rapid internalization into human prostate cancer PC-3 cells, and effective targeting of PC-3 tumors xenografted in immunosuppressed mice, whereas their excretion from the body of mice was found to be dependent on peptide length or hydrophilicity of spacers introduced between metal-chelate and peptide chain (11). Urged by the lack of studies on radioligands based on human homologs of amphibian BBN, we have recently expanded our research activities toward human peptide sequences, such as the 27-mer GRP and its Cterminal decapeptide fragment GRP (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), otherwise referred to as neuromedin C (3,12). Hence, we have recently introduced 99m Tc-demomedin C, formed by coupling an acyclic tetraamine chelator to the primary amine of Gly 18 of GRP (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) to allow for labeling with 99m Tc (13).…”
mentioning
confidence: 99%